Paving the Way to a New India by Enhancing Employability Skills among MBA Students: A Thematic Analysis (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
India has long been recognized for its rich educational heritage, with a system that dates back to the Vedic period. Today, the nation continues this legacy with a vast and expanding network of institutions offering a diverse range of professional courses, with a significant focus on management programs. However, as the number of MBA graduates increases, so do the challenges they encounter in securing employment. Numerous studies and surveys have highlighted a concerning trend: while the quantity of MBA graduates has grown, there has been a noticeable decline in the average quality of their employability skills.